2020
DOI: 10.3389/fimmu.2020.00240
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to Targeting B Cells for Myasthenia Gravis Therapy

Abstract: Current therapies for myasthenia gravis (MG) are limited, and many investigations have recently focused on target-specific therapies. B cell-targeting monoclonal antibody (mAb) therapies for MG are increasingly attractive due to their specificity and efficacy. The targeted B cell biomarkers are mainly the cluster of differentiation (CD) proteins that mediate maturation, differentiation, or survival of pathogenic B cells. Additional B cell-directed therapies include non-specific peptide inhibitors that preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 85 publications
(78 reference statements)
0
27
0
Order By: Relevance
“…While the full BEAT-MG results are currently unpublished, there may be other reasons for the negative results such as the potential development of human antichimeric antibody (HACA) against RTX. Also, since long lived plasma cells lacking CD20 are not targeted by RTX, any clinical benefits may be transient and would require chronic infusions—beyond the 2 cycles in the study— to maintain the effects ( 76 ).…”
Section: Direct B Cell Depletorsmentioning
confidence: 99%
“…While the full BEAT-MG results are currently unpublished, there may be other reasons for the negative results such as the potential development of human antichimeric antibody (HACA) against RTX. Also, since long lived plasma cells lacking CD20 are not targeted by RTX, any clinical benefits may be transient and would require chronic infusions—beyond the 2 cycles in the study— to maintain the effects ( 76 ).…”
Section: Direct B Cell Depletorsmentioning
confidence: 99%
“…Experimentally, the investigational RNAi targeting C5 (Kusner et al, 2019) and the single-chain AChR antibody coupled to complement decay-accelerating factor (Kusner et al, 2014) are shown to be efficacious in the models of MG. Promising therapeutic strategies include the B cell-related therapies (Rituximab; Tandan et al, 2017;Beecher et al, 2019;Di Stefano et al, 2020;Huda, 2020;Litchman et al, 2020) and the neonatal Fc receptor antagonists (Efgartigimod and Rozanolixizumab; Ulrichts et al, 2018;Howard et al, 2019;Huijbers et al, 2019a;Zuercher et al, 2019;Gable and Guptill, 2020). Taking into consideration of the reduced suppressive activity of T regulatory cells (Treg) in MG (reflecting on elevated inflammatory cytokines in MG; Thiruppathi et al, 2012;Ha and Richman, 2015;Wen et al, 2016;Molin et al, 2017), the Treg-based therapy achieved with the use of IL-2/anti-IL-2 monoclonal antibody complexes could be useful for treating MG as shown by the experiment in experimental autoimmune MG (Liu et al, 2010;Danikowski et al, 2017).…”
Section: Anti-achr Antibodiesmentioning
confidence: 99%
“…The patients respond to immunosuppressant therapy (Evoli et al, 2008(Evoli et al, , 2018Pasnoor et al, 2010;Guptill et al, 2011;Evoli and Padura, 2013;Koneczny et al, 2014;Morren and Li, 2018;Li et al, 2019). The B-cell depletion therapy (Rituximab) provides more benefit to MuSK-MG patients than AChR-MG patients (Evoli et al, 2008(Evoli et al, , 2018Díaz-Manera et al, 2012;Evoli and Padura, 2013;Tandan et al, 2017;Morren and Li, 2018;Beecher et al, 2019;Di Stefano et al, 2020;Huda, 2020;Litchman et al, 2020). In the experimental model of MuSK MG, the fetal Fc receptor antibodies (Gable and Guptill, 2020), antigenspecific immunoadsorption (Skriapa et al, 2014; and the inhibition of tyrosine phosphatase inhibitor (SHP2; Huda et al, 2020) alleviate the MuSK antibody-induced AChR cluster deformation.…”
Section: Anti-musk Antibodiesmentioning
confidence: 99%
“…It is known that T1D is affiliated with the loss of tolerance by autoreactive (islet-reactive) B cells [ 90 , 91 ]. B lymphocytes (cells), in addition to T lymphocytes (cells), work directly with the adaptive immune system to produce cellular and humoral defense mechanisms for protection against infections or tumors [ 90 , 92 ]. Therefore, the depletion of B cells makes an individual highly vulnerable to opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%